Mauer im Kopf - En analys av Der Spiegels samtida Östtysklandsdiskurs artikulerad under perioden januari-mars 2025 - Aronsson,Anna (2025)
This essay analyzes all articles published by Der Spiegel between January and March 2025 that discusses the discourse surrounding today’s East Germany. It examines how Der Spiegel portrays East German politics and East German political culture, as well as the explanations the magazine offers for the polarization between today's East and West Germany. This issue is particularly salient in light of the new elections in Germany in February 2025, in which the far-right Alternative für Deutschland (AfD) achieved record success in the former GDR, while the left party, Die Linke, received significant support in former East Berlin. Discourse analysis is used as both the theoretical framework and methodological tool, with a focus on critical discourse analysis (CDA) and Fairclough’s three-dimensional model. The analysis is structured around four thematic areas: democracy and the people, language and culture, migration and asylum, and extremism. The essay aims to systematically map and critically examine Der Spiegel’s contemporary discourse on East Germany.
Keywords: Der Spiegel; Östtyskland; diskursanalys; polarisering; politisk kultur; Europastudier